Influence of mechanical correction on the geometric and mechanical properties of cold-formed periodic profile fittings - L. V. Loktionova (Литьë и металлургия)
The article describes the process of mechanical correction of cold-formed fittings produced in coils on industrial rightsized cutting machines of rotary and roller types. The main qualitative characteristics of the reinforcement are given, such as: ultimate tensile strength, offset yield stress, the ratio of ultimate tensile strength offset yield stress, conditional yield strength, total elongation at maximum load and the relative area of crumpling. To assess the effect of mechanical correction on the properties of cold-formed periodic profile fittings, statistical data is used for testing samples of fittings produced in coils and straightened before manual testing and samples of the same fittings transferred from consumer companies after mechanical correction on right-sized rotary type cut machines.Tensile testing of samples was performed on testing machines in the laboratory of physical and mechanical tests No. 3 of the OJSC «BSW – Management Company of the Holding «BMC» in accordance with the requirements of ISO 15630-1:2010 «Steel for concrete reinforcement and pre-stressing. Test method. Part 1. Reinforcing rods, wire rod and wire» and ISO 6892:2016 «Metal Materials. Tensile test. Part 1. Method of test at ambient room temperature».